Theoretical design of CMOS SAW resonator - Soeroso, Iksannurazmi Bambang; Nordin, Anis Nurashikin (2012)
Traditionally, surface acoustic wave (SAW) resonators are key components in transceiver systems. SAW devices can act as high pass or low filters, high quality resonators and are usually fabricated on piezoelectric substrates such as quartz or lithium niobate. Recently, there has been interest to design the SAW devices using complementary metal-oxide semiconductor (CMOS) or integrated circuit fabrication techniques. This allows the SAW device to be integrated with circuits, yielding low cost and small device size. Generally, a separate deposition steps is being used to implement resonator's interdigital fingers (IDT). This work presents the theoretical model of a SAW resonator designed in CMOS technology. The device will be designed to minimize losses due to the piezoelectric material and to achieve high quality factors. Critical device parameters such as periodic spacing, number of transducers and reflectors are calculated based on the device's design equations. The admittance and frequency response of the device is also modeled based on the theoretical equations.